BATU BEJAMBAN ( LEGENDA MASYARAKAT PALOH DI KABUPATEN SAMBAS) - Jelita, Bela Anggun; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractBatu Bejamaban by legend of Paloh District, Sambas Regency. Legend is a folk tale that is considered truly happening, whose story is connected with historical figures, has bees flavored with miracles, and the characters special the South Coast Queen visting Palohâ€™s Kingdom. This becomes a working idea from the dance work Batu Bejamban which is presented in the form of dramatic dance or dance that tells stories. Batu Bejamban choreograph applies and goes throungh some methods, in its making â€“ process such as exploration, processing, application, evaluation, and revision. It is necessary because in writting as weel needs a systematic process simplify the writing in order to make it proper as determined concept. This is not just an enteraining performance, but it consists innovation in developing traditiona dance, educational aspect and as well morality massage. This work is expected to be reference in developing dances from West Kalimantan and could be implemented in art and Culture subject for 2nd grade students in school.Â Keyword : Batu Bejamban, Legend, Method and Creational Process, Dance Analyzing.